2018
DOI: 10.21608/jpp.2018.35233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodic Deficit Irrigation at Different Fruit Growth Stages on Yield and Fruit Quality of "Anna" Apple Trees.

Abstract: This study was carried out during two successive growing seasons 2016 and 2017 at a private farm located at El-Nubaria, Beheira governorate, Egypt to study the effect of irrigation deficit at different growth stages on some vegetative growth parameters, yield and fruit quality of "Anna" apple trees. The obtained data showed that, the highest mean values for studied vegetative growth parameters such as shoot length, shoot diameter, leaf area and specific leaf weight , yield (kg/tree -ton/fed.), fruit set percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…'Ninfa', only the most severe water deficit treatment lowered SVG considerably (Figure 6B). Many previous studies showed that yearly vegetative growth significantly decreased in the DI treatments on apricot [11,18,66], pomegranate [43], lemon [67,68], peach and pear [6,61,[69][70][71][72], apple [7,73], sweet cherry [49,[74][75][76], and olive [77]. Consequently, the RDI technique can be a useful tool to manipulate vegetative growth [78,79].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…'Ninfa', only the most severe water deficit treatment lowered SVG considerably (Figure 6B). Many previous studies showed that yearly vegetative growth significantly decreased in the DI treatments on apricot [11,18,66], pomegranate [43], lemon [67,68], peach and pear [6,61,[69][70][71][72], apple [7,73], sweet cherry [49,[74][75][76], and olive [77]. Consequently, the RDI technique can be a useful tool to manipulate vegetative growth [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…For improving the water use efficiency, a suggested irrigation strategy for fruit trees is the deficit irrigation (DI) practice especially in the arid and semiarid regions [4][5][6]. The DI practice is based on the knowledge of tree phenological stages and their responses to DI [2,7]. In order to study the benefits of DI, the crop water productivity (CWP) was proposed, which is the ratio of the yield and the consumed water by the crop [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Anna" apple is considered one of the leading apple cultivars in Egypt, being of low chilling requirements. It needs chilling about 300-350 h below 7.2°C to break their bud dormancy (Soliman et al 2018). The cultivated area of "Anna" apple cultivar is being increased rapidly especially during the last three decades to reach 66869.05 feddan in 2018 which produced 704727 ton according to FAO (2018).…”
Section: Introductionmentioning
confidence: 99%